Quadros em revista e o lugar de uma produção (1985-1992) - Bezerra, Taciana Souza (2024)
This dissertation identifies representative frames of the architectural scene published by the specialized magazines Projeto and AU in the period from 1985 to 1992 and, based on them, discusses the place that architecture produced in the Northeast region occupies in the scope of criticism and projects in these editions. The resumption of specialized periodicals in the 1970s constituted the reestablishment of communication channels between architects and occurred in parallel with the restructuring of debates in Brazil. The emergence of Projeto magazine (1972) and, when it was already consolidated, in the mid-1980s, the launch of AU magazine (1985), were milestones in this process. These two magazines brought news, criticism and projects on the most varied topics to the national architecture scene and, for many years, they were responsible for disseminating such content. In this same phase, the consolidation and multiplication of undergraduate and postgraduate centers reinforced this favorable intellectual environment for the production of texts on 20th century architecture in Brazil. Based on the themes and meta-events highlighted in the editions, as well as the editorial perspectives of the magazines Projeto and AU, with greater frequency and longevity in those years, tables were first drawn up that dealt with the conjunctures and interests related to architecture in that period so that, in then, trace the relationships between the architecture produced in the Northeast that is published and the discussions held in this scenario. In this way, it was possible to reflect on the place of this production within the national framework, as well as on its representation in these two vehicles.